HYDration and Bicarbonate to Prevent Acute Renal Injury After Endovascular Aneurysm Repair With Suprarenal Fixation: Pilot/Feasibility Randomised Controlled Study (HYDRA Pilot Trial). (May 2018) - Saratzis, Athanasios; Chiocchia, Virginia; Jiffry, Ahmad; Hassanali, Neelam; Singh, Surjeet; Imray, Christopher H.; Bown, Matthew J.; Mahmood, Asif
Abstract : Objective/Background: Up to 25% of patients undergoing elective endovascular aneurysm repair (EVAR) develop acute kidney injury (AKI), which is associated with short and long-term morbidity and mortality. There is no high quality randomised evidence regarding prevention of EVAR related AKI. Methods: A novel AKI prevention strategy for EVAR was devised, based on best evidence and an expert consensus group. This included a bolus of high dose sodium bicarbonate (NaHCO3 ) immediately before EVAR (1 mL/kg of 8.4% NaHCO3 ) and standardised crystalloid based hydration pre- and post-EVAR. A pilot/feasibility randomised controlled trial (RCT) was performed in two centres to assess the safety of the intervention, potential impact on AKI prevention, and feasibility of a national RCT; the primary end point was the proportion of eligible patients recruited into the study. AKI was defined using "Kidney Disease Improving Global Outcomes" and "Acute Kidney Injury Network" criteria based on National Institute for Health and Clinical Excellence AKI recommendations, using serum creatinine and hourly urine output. Results: Fifty-eight patients (84% of those screened; median age 75 years [range 57–89 years], 10% female) were randomised to receive the standardised intravenous hydration with (intervention) or without (control) NaHCO3 . Groups were comparable in terms of AKI risk factors; 56 of 58 participants had a device with suprarenal fixation. Overall, 33% of patients in the control arm developed AKI versus 7% in the intervention arm (as treated analysis). None of the patients receiving NaHCO3 developed a serious intervention related adverse event; five patients did not attend their 30 day follow-up. Conclusion: Bolus high dose NaHCO3 and hydration is a promising EVAR related AKI prevention method. This trial has confirmed the feasibility of delivering a definitive large RCT to confirm the efficacy of this novel intervention, in preventing EVAR related AKI.